ESQ dan Kebutuhan Spiritualitas Civitas Akademik - Asep Solikin (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
The truth is that humans are religious (homoreligius) beings and their fithrah is a spiritual being who always strives to always be in a healthy mental state, so that a happy, inner and inner life. He has the perfect spiritual intelligence potential to achieve